Availability and use of woody plants in a agrarian reform settlement in the cerrado of the state of Goiás, Brazil - Tunholi, Vanessa Pessanha (2013)
Protected areas are important sources providing plant resources for human populations, and contributing to the livelihood and income of families. To test the ecological apparency hypothesis, that there is positive relationship between the visibility of a species and its use, we conducted an ethnobotanical survey in the protected area of the Itaúna rural settlement in the municipality of Planaltina, in the state of Goiás, in central Brazil. The phytosociological parameters were obtained in 5.6 ha area of the Brazilian cerrado (savanna), and the ethnobotanical survey conducted with semi-structured interviews with 75 people. There was a weak positive correlation between the use value and the phytosociological parameters. A principal component analysis showed that seven species (Pterodon pubescens, Hancornia speciosa, Hymenaea stigonocarpa, Eugenia dysenterica, Annona crassiflora, Stryphnodendron adstringens and Solanum lycocarpum) have high use value, despite having low density, dominance and frequency. Nineteen species showed a positive relationship between their use value and their phytosociological parameters. The relationship between vegetation structure and use value differed among species in the protected area, indicating that more attention should be paid to those under more pressure, with low abundance. Further studies of these seven species should be conducted to determine whether human pressure is affecting populations structures and to define management strategies.